Pengembangan Media Pembelajaran Aktivitas Bela Diri Melalui Audio Visual untuk Sekolah Menengah Pertama di Masa Pandemi Covid 19 (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the level of success of the product that has been developed in the form of learning media for self-defense activities through audio-visual for grade VII junior high school students. This research is a development research (R&D). This research procedure is carried out through the potential and problem stages, data collection, making initial product designs, validation of media experts and material experts. Furthermore, the product was tested on students and physical education teachers through small group trials, revisions, large group trials, and product revisions. The subject of the product trial was class VII SMP N 4 Wadaslintang. The test subjects were large groups of seventh grade students at MTS Kaligowong, and Islamic Middle School Wadaslintang. The results of material expert validation from the aspect of learning quality got a score of 21